The time of enlightenment - Nelson, William Max (University of Toronto Press, 2021)
Making Time Different: Historical Change and the Laws of Nature – Living the Future: Ideas of Progress and Uncanny Temporality – “The Explosion of Light”: The Economic Order and the Scientific Revelation of the Future – Generating Time: Buffon and the Biological Instruments of Futurity – The Time of Regeneration: Renewal, Rupture, and Beginning Anew in the French Revolution.
Literaturverzeichnis Seite [155]-214
Keywords: Enlightenment; Forecasting; Future; The; Philosophy; French; Enlightenment; Influence; Intellectual life; History